2019
DOI: 10.1126/scitranslmed.aba1659
|View full text |Cite
|
Sign up to set email alerts
|

Promising disease-modifying therapies for Parkinson’s disease

Abstract: To date, there is no disease-modifying therapy for Parkinson’s disease; however, promising new agents have advanced into clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 10 publications
0
55
0
Order By: Relevance
“…The major ndings of this paper are the observation that celastrol protects against the loss of dopaminergic neurons and maintains the nigro-striatal system function, and attenuates the motor de cit in both MPTP-induced and human α-synuclein overexpression-induced PD mouse model. It's well established that the hallmark of PD is the loss of dopaminergic neurons [6,8,39,62,63]. Recently, the glia (astrocyte and microglia) mediated neuroin ammation has been found to play critical roles in the pathologies of PD [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The major ndings of this paper are the observation that celastrol protects against the loss of dopaminergic neurons and maintains the nigro-striatal system function, and attenuates the motor de cit in both MPTP-induced and human α-synuclein overexpression-induced PD mouse model. It's well established that the hallmark of PD is the loss of dopaminergic neurons [6,8,39,62,63]. Recently, the glia (astrocyte and microglia) mediated neuroin ammation has been found to play critical roles in the pathologies of PD [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the glia (astrocyte and microglia) mediated neuroin ammation has been found to play critical roles in the pathologies of PD [38][39][40]. It's recently reported that GLP-1 receptor agonists (exenatide, NLY01) may prevent pathological microglial activation and secretion of the proin ammatory cytokines (TNFα, IL1) to prevents the conversion of resting astrocytes to the toxic and reactive A1 phenotype; and Amylin Pharmaceuticals' and AstraZeneca's GLP-1 receptor agonist exenatide and Novo Nordisk's Liraglutide, Sano 's Lixisenatide, and Neuraly's NLY-01 are in placebo-controlled phase 2 trial in patients with moderate PD [8,48,64]. These reports show that both the dopaminergic and neuroin ammation-targeting therapies may contribute to the development of PD treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although mechanistic studies have made some important discoveries, there is still no cure for PD. However, breaking through a therapeutic approach that can modify disease progression is very limited to pilot clinical studies or animal experiments [6,7]. In this context, dopamine replacement remains the gold standard to relieve motor symptoms [6].…”
mentioning
confidence: 99%
“…However, breaking through a therapeutic approach that can modify disease progression is very limited to pilot clinical studies or animal experiments [6,7]. In this context, dopamine replacement remains the gold standard to relieve motor symptoms [6]. In the past few years, a non-dopaminergic drug that targets the adenosine A2A receptor has been approved as an adjunct therapy for PD [8,9].…”
mentioning
confidence: 99%